2018
DOI: 10.3390/rs10101510
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Response of Sun-Induced Fluorescence and PRI to Water Stress in Maize Using a Near-Surface Remote Sensing Platform

Abstract: Sun-induced Fluorescence (SIF) and Photochemical Reflectance Index (PRI) data were collected in the field over maize to study their diurnal responses to different water stresses at the canopy scale. An automated field spectroscopy system was used to obtain continuous and long-term measurements of maize canopy in four field plots with different irrigation treatments. This system collects visible to near-infrared spectra with a spectrometer, which provides a sub-nanometer spectral resolution in the spectral rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…Numerous studies have found that the leaf F q /F m is linearly related to the canopy SIF based on ground measurements [17,18]. This linear relationship is the scientific basis for the application of SIF in detecting the gross primary productivity (GPP) at various ecosystem levels, because SIF and GPP can be separately calculated as: SIF = SIF yield × APAR and GPP = PSII operating efficiencey × APAR.…”
Section: Implications From the Nonlinear Relationship Between Sif Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have found that the leaf F q /F m is linearly related to the canopy SIF based on ground measurements [17,18]. This linear relationship is the scientific basis for the application of SIF in detecting the gross primary productivity (GPP) at various ecosystem levels, because SIF and GPP can be separately calculated as: SIF = SIF yield × APAR and GPP = PSII operating efficiencey × APAR.…”
Section: Implications From the Nonlinear Relationship Between Sif Andmentioning
confidence: 99%
“…Thus, the linear relationship between SIF and GPP is briefly determined by the ratio LUE P /LUE F (λ). A mass of evidence based on experimental measurements has shown that the relationship between LUE P and LUE F (λ) (i.e., the SIF yield at 760 nm) is linear [17,18], which means that the value of LUE P /LUE F (λ) remains relatively constant and GPP is linearly related to SIF in a specific ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In reference to previous research [ 13 , 24 , 31 , 32 , 33 , 34 ], based on the characteristics of this study and combined with the physical meaning of the VI, we evaluated 13 VIs ( Table 1 ) in relation to the canopy structure, chlorophyll, soil adjustment, and physiological response to stress. We also selected some red-edge VIs that had a good estimate effect for the FPAR, according to Dong et al (2015) [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…These results show that instantaneous NDVI measurements provide a stable and near-linear estimate of the diurnally integrated FPAR in an herbaceous vegetation canopy as long as the remotely sensed observations are taken when the solar zenith angle is above 60° and the sensor views are within 40° of the nadir [ 14 ]. Recent in situ measurements, however, show that the FPAR may fluctuate dramatically within a day because of changes in the light conditions [ 23 ] and stress states [ 24 ]. The FPAR diurnal course of an alpine wetland showed a “bowl-shaped” pattern, which was small around noon but larger in the early morning (before 10:00) and mid-afternoon (after 14:00) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation